SISTEM INFORMASI PENJUALAN TIKET MASUK WISATA JEMBATAN CINTA BERBASIS WEB - Jefi Jefi; Muhammad Fahmi; Hendri Hendri; Desiana Nur Kholifah; Suharjanti Suharjanti (INTI Nusa Mandiri, 2023)
Abstract— The use of technology in the tourism industry is becoming increasingly crucial considering changes in consumer behavior that tend to rely on digital platforms to make transactions. To analyze the effectiveness and reliability of facilitating the process of purchasing tickets online. In addition, it also includes an evaluation of the level of user satisfaction with this web-based system and its impact on increasing visits to the Cinta Bridge tourist attraction. Through surveys of tourists using a web-based ticket sales system, interviews with tour managers, and analysis of ticket transaction data documented in the system. Research participants include tourists, managers, and other related parties. The data were obtained and analyzed using statistical methods and qualitative analysis to gain a thorough understanding of the impact of the Web-Based Bridge Tourism Entrance Ticket Sales Information System. Demonstrating that managing ticket stock and arranging visit schedules more efficiently is also a positive result for the development of the technology-based tourism industry by proving the benefits of the Web-Based Bridge of Love Entrance Ticket Sales Information System. The results of this study can be the basis for the development and implementation of similar systems in other tourism destinations. In addition, the research is considered to provide valuable insights for related parties in optimizing the use of technology to improve user experience and operational efficiency in the tourism sector